Загальні ознаки медіафейків у повідомленнях російської антиукраїнської пропаганді - Ковкіна, Євгенія Володимирівна; Баранська, Наталія Володимирівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
A modern, non-classical form of implementing Russian aggressive policy is the destabilization of the socio-political situation in Ukraine by spreading media fakes. Draws attention to the need to identify and analyze information that poses a threat to the information security of Ukrainian statehood. It is emphasized that one of the main tools of manipulation of public opinion is media fake. A general interpretation of a media fake is given, and its typical signs are outlined. Manipulation is one of the accompanying mechanisms for spreading fake information. Here is an example of a common media fake that demonstrates a tool of opinion manipulation. Conclusions were drawn that anti-Ukrainian Russian propaganda is based on the introduction of historical myths and media fakes.